Exploring the Future Workforce of Palm Oil Industry: A Study of Student Career Interests in Riau, Indonesia - Boris Kaido; Feri Agriani; Sri Oktika Syaputri; Afdhal Afdhal; Abdul Rahman Saili (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The palm oil industry has significantly contributed to poverty alleviation and job creation, employing approximately 16 million workers in Indonesia. However, this economic opportunity is accompanied by a lack of interest among students in pursuing careers in this sector, primarily due to negative perceptions and the nature of the sector. This study examines students’ perceptions and career interests in the palm oil industry, along with the factors shaping these interests, focusing on Kampar Regency, Riau—a major palm oil hub in Indonesia. Using proportional purposive sampling, 332 participants were selected from a population of 694. : In this research during the year 2023-2025, Kampar district is selected for the study. The research conducted a survey among students in Kampar district, Riau province, which is recognized as one of the major hubs for palm oil production in Indonesia, utilizing a proportional purposive sampling method. A total of 332 participants were selected from a population of 694 individuals. Descriptive analysis was used to fulfill the first objective, while logit regression analysis was performed to meet the second objective. The results revealed that most students come from rural backgrounds, and many of their parents are engaged in the palm oil industry. Parental palm oil land ownership is highest at 0-4 hectares, and parental income is highest at IDR 0-2 million. In summary, parents have the greatest influence on the career choices of students, and the only factor influencing students' interest in pursuing a future career in the palm oil plantation sector was the level of education of the father.